2011
DOI: 10.1002/ijc.26012
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose docetaxel enhances the sensitivity of S‐1 in a xenograft model of human castration resistant prostate cancer

Abstract: S-1 is a recently developed dihydropyrimidine dehydrogenase inhibitor fluoropyrimidine and has demonstrated high maximum plasma 5-Fluorouracil (5-FU) levels with mild toxicity, and an oral formulation has resulted in an improvement in patient quality of life. The aims of the present study were to determine the efficacy of S-1 or S-1 combined with docetaxel (DOC) using castration resistant prostate cancer (CRPC) cells and to explore their clinical potential for treating CRPC patients. LNCaP cells, androgen depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…These changes in enzymes that metabolize 5-FU might clarify the enhanced effect of S-1 combined with docetaxel. As reported by Hasegawa et al, a similar synergistic effect is observed in castration-resistant prostate cancer [12]. Interestingly, in the xenograft model, S-1 with low-dose docetaxel could enhance the antitumor effect of S-1.…”
Section: Discussionsupporting
confidence: 80%
“…These changes in enzymes that metabolize 5-FU might clarify the enhanced effect of S-1 combined with docetaxel. As reported by Hasegawa et al, a similar synergistic effect is observed in castration-resistant prostate cancer [12]. Interestingly, in the xenograft model, S-1 with low-dose docetaxel could enhance the antitumor effect of S-1.…”
Section: Discussionsupporting
confidence: 80%
“…26, 36 Similarly, low-dose DTX is an effective and well-tolerated treatment for mCRPC, 37, 38 and also enhanced the anti-tumor effects of several therapeutic agents in prostatic xenografts. 31, 39, 40, 41 …”
mentioning
confidence: 99%
“…We have previously reported a useful model of human CRPC202122232425. Briefly, we cultured the PTEN-null, androgen receptor (AR) positive, PSA producing CRPC cell line C4-2 for more than 6 months under androgen ablation conditions and named it C4-2AT6.…”
mentioning
confidence: 99%